The Sustainability of Life Approach: A State of Affairs. - Agenjo-Calderón, Astrid (Feminist Economics, 2023)
This article explores the main features of the "sustainability of life" approach, a theoretical and political approach specifically developed in the context of Spanish, Latin American, and Caribbean feminist economics in the last two decades. It dialogues with decolonial feminisms; ecofeminisms and degrowth ecological proposals; the popular, social, and solidarity economy; and feminist reflections on "good living" and "good co-existence." The article situates this approach within the wider spectrum of feminist economics as a plural school of thought and examines its particular characteristics in greater detail. Specifically, the article highlights sustainability of life as a multilevel approach that connects economic, social, and ecological systems and reveals the capital-life conflict that runs through them; offers a non-Eurocentric and intersectional perspective for analyzing the diverse implications of this conflict; and presents a political positioning that draws emancipatory imaginaries and horizons that place life at the center. Sustainability of life has come to be a main theoretical approach of Spanish, Latin American, and Caribbean feminisms. It offers an emancipatory roadmap for organizing life outside of capitalist structures. It proposes a vision for constructing an economy that is feminist, plural, and inclusive, prioritizing women and peripheral subjects. It presents a political proposal for collective action to confront the logic of capitalist, patriarchal, and racist systems. It harbors as its ultimate goal the sustaining of a "good collective life."